Epidemiology of anterior cruciate ligament injuries in soccer - Bjordal, J. M.; Arnly, F.; Hannestad, B.; Strand, T. (The American Journal of Sports Medicine, 1997)
We did a retrospective study of all anterior cruciate ligament injuries (972) verified by arthroscopic evaluation at hospitals in the Hordaland region of Norway from 1982 to 1991. Our final study group comprised 176 patients who had participated in organized soccer and answered a questionnaire. The overall incidence rate was 0.063 injuries per 1000 game hours. Men incurred 75.6% (133) of the injuries. Women had an incidence rate of 0.10 injuries per 1000 game hours, significantly higher than that for men (0.057). The incidence rate was higher (0.41) for men in the top three divisions. Most of the injuries (124) occurred during games. Contact injuries from tackling was the injury mechanism in 46.0% of the cases. Players on the offensive team incurred 122 (69.3%) of the injuries. Reconstructive surgery was performed on 131 (74.4%) of the injured players and was found necessary for return to a high level of play. Half of the players (87) returned to soccer; men at high levels of play had the highest return rate (88.9%), and men over age 34 had the poorest return rate (22.9%). Nearly one-third of the injured athletes gave up soccer because of poor knee function or fear of new injury.